Míra pocitu ohrožení zaměstnanců a faktor stresu v kontextu jejich pracovní výkonnosti na příkladu podniku ArcelorMittal Tubular Products Karviná a. s. - Hečko, Štefan; Janečková, Petra; Malátek, Vojtěch; Řihák, Radim (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
Purpose of the article: The article concerning human resource management focuses on the employee feeling of threat level and its influence on the work performance in a specific manufacturing company in the Czech Republic. The article, firstly, defines basic safety-related terminology such as threat, fear, stress, and safety threats. Secondly, it describes perception of stress and threat, together with their influence and impact on personal and work life of an individual. Finally, it presents the results of research done among employees and top management in the company ArcelorMittal Tubular Products Karviná a. s. Methodology/methods: Methodology is based on analysis of primary data acquired from the research and analysis of secondary data from the professional literature. An explorative method of questioning was used to acquire the primary research data (a questionnaire for the employees, a semi-formalized interview for the top management). Level one of quantitative classification comparison, statistical tools of MS Excel, and Statistical Package for the Social Sciences programme were used for the purpose of the analysis. Furthermore, methods of induction, deduction were used and based on the research results suggestions of measures for the company personnel activities were stated. Scientific aim: The aim of the research is to detect the employee feeling of threat level and its influence on their work performance in the company and to suggest measures for the company personnel activities, which could be implemented by the company management in the future. Findings: This article offers a complex insight into a specific company employee safety and the employee feeling of threat level and its influence on the work performance. The article presents a set of measures for the company personnel activities, which could help increase the workflow quality. Conclusions: Suggested measures, within the company human resource management, can contribute to an increase in the employee work life quality. Employee mental temper is influenced also by the level of stress felt by the employee when getting to/from work. Good working conditions are essential for acquiring and keeping the quality and qualified employees as well as for successful existence in the high competitive national and international globalized markets.
The Level of Employees‘ Feeling of Threat and Stress Factor in Context of Their Work Performance on the Example of Company ArcelorMittal Tubular Products Karviná a. s.
Keywords: enterprise; respondent; sense of security; threat; stress; work performance